The Effect of the Six Thinking Hats Strategy on Student Grouping to Improve Problem-Solving Skills and Concept Mastery in Reaction Rate Material - Azzahra, Elvara Siti; Harjito, Harjito (Chemistry in Education, 2025)
This study aims to analyze the effect of the Six Thinking Hats strategy on enhancing students’ problem-solving skills and conceptual understanding in the topic of reaction rates. The research employed a quasi-experimental method using a non-equivalent control group design. Instruments included concept mastery tests (pretest and posttest), student worksheets (LKPD), and student response questionnaires. Data were analyzed using the Mann-Whitney U test, the Friedman test, Spearman's Rank correlation, and effect size calculations. The results showed that the implementation of the Six Thinking Hats strategy had a significant impact on the improvement of students’ problem-solving abilities and conceptual understanding, as indicated by the Mann-Whitney U test results for each LKPD (p < 0.05) and large to very large effect sizes (Cohen’s d = 1.15; 1.48; 0.56; and 2.99). The Friedman test revealed statistically significant differences in performance across LKPDs in both the experimental and control classes (p = 0.000). In terms of conceptual understanding, a significant difference was observed (p = 0.000), with an increase in Cohen’s d from 0.65 (moderate) to 2.08 (large). However, the Spearman Rank correlation test indicated no significant relationship between conceptual understanding and problem-solving ability, suggesting that individual and collaborative assessment contexts influence student outcomes differently.